Threat Analysis and Risk Assessment and Countermeasures Against Threat Scenarios for Steer-by-Wire System - Ozcetin, Okan; Emirler, Mumin Tolga (IEEE, 2024)
The advent of relevant sophisticated technologies has led to the development of numerous intelligent and interconnected vehicle functions. While this has undoubtedly enhanced drivers' quality of driving experience, it also has generated a multitude of cybersecurity vulnerabilities. One illustrative example is the evolution of the steering system. With the introduction of steer-by-wire (SbW) systems, the traditional hydraulic steering mechanism has been transformed into a more sophisticated electronic system. Furthermore, since steer-by-wire systems are networked to communicate with other connected components and systems inside and outside the vehicle, they introduce a new layer susceptible to cyberattacks. This paper is focused on the security vulnerabilities of the SbW in the context of threat analysis and risk assessment (TARA) as well as countermeasures that are advised to be considered against possible threats. The study overall sets out to provide an initial analysis and measures for achieving the cybersecurity of the SbW system. Firstly, the boundaries of the SbW as an item are demonstrated in the item definition. Subsequently, TARA and countermeasures against determined threat scenarios are represented. In the TARA, respectively, asset identification, identification of damage scenarios that compromise cybersecurity properties of assets, impact ratings of damage scenarios, identification of threat scenarios with spoofing, tampering, repudiation, information disclosure, denial of service, and elevation of privileges (STRIDE) methodology, attack feasibility rating determination, risk value/cybersecurity assurance level (CAL) determination, risk treatment decisions, and cybersecurity goal determination are addressed. Finally, countermeasures are determined against the threat scenarios based on the set cybersecurity goals.
Keywords: cybersecurity; steer-by-wire; threat analysis and risk assessment; vulnerability; Computer Science; Engineering; Telecommunications